Religiosity of Students during the Covid-19 Pandemic - Kuswandari, Yuli; Ulfah, Suci Nurmaya (Program Studi Pendidikan Agama Islam, 2022)
This study aims to identify and produce valid information about the religiousity of students during the covid-19 pandemic. It used qualitative research method anda case study approach to investigate students’s religiousity during the pandemic. This research was conducted by taking data and information from 9 respondents consisted of 5 parents and 4 children. The results of the research revealed several problems faced by students when they studied through online learning. Students knowledge on Islamic religion and their practice on Islamic teaching got worse. This greatly affected the religiousity of students during a pandemic. Some of them were not on time to do prayer and inconsistent to pray. Theya were rarely to read the holy quran.. This happene because there was not anyone who assisted them to learn. The parents were fully responsible to give guidance for their children to study at homes. Therefore, good cooperation between teacher and parents is much needed, The success of students is supported by the parents.